Seismic rehabilitation performance of steel side plate moment connections. - Chou, Chung-Che
Moment connections in an existing steel building located in Kaohsiung, Taiwan were rehabilitated to satisfy seismic requirements based on the 2005 AISC seismic provisions. Construction of the building was ceased in 1996 due to financial difficulties and was recommenced in 2007 with enhanced connection performance. Steel moment connections in the existing building were constructed by groove welding the beam flanges and bolting the beam web to the column. Four moment connections, two from the existing steel building, were cyclically tested. A non-rehabilitated moment connection with bolted web-welded flanges was tested as a benchmark. Three moment connections rehabilitated by welding full depth side plates between the column face and beam flange inner side were tested to validate the rehabilitation performance. Test results revealed that (1) the non rehabilitated existing moment connection made by in situ welding process prior to 1996 had similar deformation capacity as contemporary connection specimens made by laboratory welding process, (2) all rehabilitated moment connections exhibited excellent performance, exceeding a 4 percent drift without fractures of beam flange groove welded joints and (3) presence of the full depth side plates effectively reduced beam flange tensile strain near the column face by almost half compared with the non-rehabilitated moment connection. The connection specimens were also modeled using the non linear finite element computer program ABAQUS to further confirm the effectiveness of the side plate in transferring beam moments to the column and to investigate potential sources of connection failure. A design procedure was made based on experimental and analytical studies.
Keywords: Rehabilitated steel moment connection; Side plate; Cyclic test; Finite element analysis